2020
DOI: 10.3390/su12072895
|View full text |Cite
|
Sign up to set email alerts
|

Removing Sr(II) and Cs(I) from the Aqueous Phase Using Basil Seed and Elucidating the Adsorption Mechanism

Abstract: To confirm the capability and mechanisms of Sr(II) and Cs(I) adsorption from the aqueous phase using basil seed (BS), virgin BS, calcined BS (BS500 and BS1000), and enzymatically treated BS, namely Mannanase BGM (M-BS), Pectinase G (P-BS), Hemicellulase (H-BS), and Cellulase A (C-BS) was evaluated. The adsorption capabilities of Sr(II) and Cs(I) of various BS adsorbents were also evaluated. The quantity of Sr(II) and Cs(I) adsorbed onto BS was greater than that of BS500 or BS1000, suggesting that the physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In contrast, the signals of Lig600, Lig800, and Lig1000 were not detected because Lig600, Lig800, and Lig1000 were prepared as carbonaceous material from lignin by the calcination treatment under our experimental conditions. Previous studies have reported that the number of surface functional groups such as phenolic and carboxyl groups decreased upon carbonization at approximately 600 C (Yokoyama et al, 2008;Uematsu et al, 2020). Therefore, similar trends were observed herein.…”
Section: Effect Of Calcination On Physical Propertiessupporting
confidence: 90%
“…In contrast, the signals of Lig600, Lig800, and Lig1000 were not detected because Lig600, Lig800, and Lig1000 were prepared as carbonaceous material from lignin by the calcination treatment under our experimental conditions. Previous studies have reported that the number of surface functional groups such as phenolic and carboxyl groups decreased upon carbonization at approximately 600 C (Yokoyama et al, 2008;Uematsu et al, 2020). Therefore, similar trends were observed herein.…”
Section: Effect Of Calcination On Physical Propertiessupporting
confidence: 90%
“…Therefore, the development of recycling technology for waste biomass is urgently needed. Previous studies have reported that waste biomass such as mangosteen, wheat bran, basil seed, and agriculture wastes showed the capacity to adsorb harmful substances such as mercury, chromium, strontium, cesium, molybdenum, and dyes from aqueous media (Ogata et al, 2018(Ogata et al, , 2020a(Ogata et al, , 2020bSivarama Krishna et al, 2014;Somasekhara Reddy et al, 2012;Uematsu et al, 2020). These results indicate that the conversion from waste biomass to an adsorbent is one of the most useful techniques for reducing these wastes.…”
Section: Introductionmentioning
confidence: 78%
“…Co., Ltd. (Japan), respectively. Calcined BS at 1000 C (BS1000) was prepared by the carbonization of BS (Uematsu et al, 2020). Paraquat dichloride standard (C 12 H 14 C l2 N 2 ) and diquat dibromide monohydrate standard (C 12 H 12 Br 2 N 2 H 2 O) were purchased from FUJIFILM Wako Pure Chemical Co., Japan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being effective and low-cost, the adsorption method is more feasible than other methods of water treatment, so adsorption is a promising and common way to remove dyes from aqueous effluents [11][12][13]. Currently, a large range of adsorbent materials based on solid waste have been researched for removing dyes from aqueous solutions, such as waste coffee grounds [14], olive cake waste [15], metal hydroxide sludge [16], waste coal gangue [17], paper mill sludge [18], waste cellulose fibers [19], tannery solid waste [20], oil shale [21].…”
Section: Introductionmentioning
confidence: 99%